Combat organ trafficking – reward the donor or regulate sales - Slabbert, M. (Koers, 2008)
There is an acute shortage of transplantable human organs worldwide. The current systems of organ procurement cannot supply in the demand. A new approach is imperative. While countries struggle to find ways of motivating more people to become organ donors, the international illegal black market is thriving. A possible solution to the problem in South Africa might be to change current legislation by confirming human organ trafficking a specific crime as is the case in the United Kingdom. However, more available organs for transplantation in the current recognised system are also essential. To achieve this, it is proposed that donors should be rewarded more effectively, or a regulated market in human organs should be allowed.